1978
DOI: 10.1007/bf03350390
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hyperglycemia on the growth hormone response to L-dopa in diabetic subjects

Abstract: Plasma growth hormone (GH) levels were measured before and after oral administration of L-dopa in 8 insulin-dependent juvenile diabetic patients, and in 6 non insulin-dependent maturity-onset diabetics, while they were hyperglycemic, and values were compared with those of normal children and adult subjects. Maturity-onset diabetics failed to show an increase in serum GH levels after L-dopa administration, while serum peak GH values of juvenile diabetic patients were not significantly different from those of no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1987
1987
1987
1987

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In vitro and in vivo studies demonstrated that calcium antagonists (CA) may affect the basal and/or the stimulated secretion of several hormones (Millard and Struthers 1984). In vivo, verapamil inhibited TRH-stimulated TSH release ( Barbarino and de Marinis 1980). However, the effect of CA at thyroid level has never been studied.…”
mentioning
confidence: 99%
“…In vitro and in vivo studies demonstrated that calcium antagonists (CA) may affect the basal and/or the stimulated secretion of several hormones (Millard and Struthers 1984). In vivo, verapamil inhibited TRH-stimulated TSH release ( Barbarino and de Marinis 1980). However, the effect of CA at thyroid level has never been studied.…”
mentioning
confidence: 99%
“…Nineteen of the 28 4'°c m/y or greater and a predicted wt height less than the target adult height for the family by more than 2.5 SDs.…”
mentioning
confidence: 99%